The Role of Self-Acceptance and Self-Confidence in Quarter-Life Crisis Among Early Adulthood in Medan - Aritonang, Nancy Naomi Gabe Parsaulian; Simarmata, Nenny Ika Putri; Simalango, Yohana Stefani; Siregar, Theresia Naftalia; Primus, Lewi (Journal of Educational, Health and Community Psychology, 2025)
The transition from adolescence to early adulthood involves various emotional and social challenges. This study examined the relationship between self-acceptance and self-confidence with quarter-life crisis among early adults in Medan. Using a quantitative design and purposive sampling, data were collected from 369 individuals aged 20–40 years through Likert-type psychological scales. Data analysis using multiple linear regression showed that both self-acceptance and self-confidence significantly correlated with quarter-life crisis (p < 0.05), with an R² value of 0.336. This indicates that the two variables explain 33.6% of the variance in quarter-life crisis. Higher self-acceptance and self-confidence were associated with lower levels of quarter-life crisis. The novelty of this study lies in its focus on internal psychological factors in an Indonesian urban context. These findings underscore the importance of psychological support programs in enhancing self-perception and resilience among young adults.